(untitled) - Epstein, Eve (New York, 2014)
Seen through the eyes of siblings 14 years apart in age, X vs. Y is a smart, funny, stylish, and visually driven anthology that compiles and compares their two generational cultures. It’s a story told through lists, infographics, essays, anecdotes, and images, with chapters devoted to fashion,TV, music, technology, dating, books, and movies. Through musings on topics such as leg warmers, Clueless, Sassy magazine, and MTV, along with mixtapes and TV characters, X vs. Y paints a portrait of two intricately entwined generations.
Keywords: Youth,Generation,Popular culture,Thiếu niên,Thế hệ,Văn hóa phổ biến; Hoa Kỳ; 20th century,Thế kỷ 20; United States,United States,United States,Hoa Kỳ,Hoa Kỳ